The importance of transport infrastructure management - Hasan, Nurul Liyana; Anuar, Nur Khairiel (2012)
This paper evaluates the transport infrastructure in Arau, Perlis, Malaysia. Arau is the royal capital of Perlis. Arau is also listed as one of the tourist attractions for visitors. Overall, road infrastructure consists of highway, road, traffic light, bridges, and bus stop. Therefore, the researcher interested in assessing the main problems encountered and identify the level of public satisfaction on the infrastructure provided.So, data was obtained using questionnaires and analysis recommendations towards problem solving were provided in Arau, Perlis, Malaysia.